Integrating The Credit Lending Strategies of Multi-Purpose Cooperatives (a Case Study at KSU Dauh Ayu in Denpasar) - I Made Gita Rivaldo; Ni Putu Nina Eka Lestari; Gede Sri Darma; A.A.N. Eddy Supriyadinata Gorda (Institute of Computer Science (IOCS), 2021)
This study aims to explore credit distribution strategies in Multipurpose Cooperatives. The research was conducted at Dauh Ayu Multipurpose Cooperative, which is one of the top performing cooperatives in Denpasar City. This study uses primary data sources with qualitative data types with data collection techniques through observation, interviews, and documentation studies with the chairman, employees and members of the Dauh Ayu Multipurpose Cooperative Denpasar. The results of this study are to increase credit distribution at the Dauh Ayu Multipurpose Cooperative, apart from implementing the 4P marketing mix (Product, Price, Promotion, Place) it also implements optimal service. The need for innovation and strategy in delivering information that is clear and easy to understand in delivering products owned by the Dauh Ayu Multipurpose Cooperative.